Multimodal Study of Adult-Infant Interaction: A Review of Its Origins and Its Current Status - Soledad Carretero Pérez; Silvia Ana Español (Paidéia (Ribeirão Preto))
Abstract An interpretative review of research on adult-infant interactions involving the analysis of movement behaviors is presented, systematically linking previous studies to current research on the subject. Forty-two articles analyzing the dyad's interactive movement in the period 1970-2015 were found. Twelve papers were excluded, including only those that studied the phenomenon in the baby's first year of life. The results revealed that movement was a central topic in early interaction studies in the 70s. In the 1980's and 1990's, its study was marginal and it is currently resurging under the embodiment perspective. The conceptual framework and research methods used in the pioneering work are presented, and the thematic foci shared with current research are highlighted. Thus, essential keys are provided for the updated study of early interactions from a multimodal perspective.